PENGARUH MANAJEMEN KELAS TERHADAP KEAKTIFAN BELAJAR PESERTA DIDIK DI MA DDI HASANUDDIN KABUPATEN MAROS - Umam, Muh. Haerul; Wahyuddin; Nursita, Lisa; Mardhiah (Department of Islamic Education Management, 2023)
This study examines classroom management on the learning activities of students at MA DDI Hasanuddin, Maros Regency, which has the aim of knowing the effect of class management on student learning activities in MA DDI Hasanuddin, Maros Regency. Ex post facto quantitative research, the population in this study were all students in MA DDI Hasnuddin Maros Regency, the sample of this study amounted to 90 students. The results of this study indicate that class management is in the moderate category with a total frequency of 62 students (69%) and the active learning of students is in the medium category with a total frequency of 65 students (72%). The results of tcount = 15,1072012 > ttable = 1,66235. There is an influence between classroom management on the learning activities of students at MA DDI Hasanuddin, Maros Regency, this means that the better the implementation of classroom management, the better the learning activities of students.